2015
DOI: 10.1021/acsnano.5b03053
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and Energy Contributions for Transport of Unfolded Pertactin through a Protein Nanopore

Abstract: To evaluate the physical parameters governing translocation of an unfolded protein across a lipid bilayer, we studied protein transport through aerolysin, a passive protein channel, at the single molecule level. The protein model used was the passenger domain of pertactin, an autotransporter virulence protein. Transport of pertactin through the aerolysin nanopore was detected as transient partial current blockades as the unfolded protein partially occluded the aerolysin channel. We compared the dynamics of ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 85 publications
3
61
0
1
Order By: Relevance
“…4, panel Boltzmann constant, Tm the absolute temperature and I= ∑ is the ionic strenght of electrolyte, zi and Ci stand for the counterions valence number and their concentration in molar units), which is low relative to the average diameter of the α-HL's β-barrel (∼20 Å) or is vestibule (∼46 Å). For our system, the average diameters of the peptide's ends estimated with the Swiss-PdbViewer were ∼13.2 Å (E12) and ∼18 Å (R12); knowing that the diameter of the α-HL's β-barrel is ∼20 Å, it is conceivable that the peptide's ends will still experience electrostatic interactions with the inner surface of the β-barrel, in agreement with previous findings on different systems [36,59].…”
Section: The Case Of Peptide Association To the Nanoporesupporting
confidence: 91%
“…4, panel Boltzmann constant, Tm the absolute temperature and I= ∑ is the ionic strenght of electrolyte, zi and Ci stand for the counterions valence number and their concentration in molar units), which is low relative to the average diameter of the α-HL's β-barrel (∼20 Å) or is vestibule (∼46 Å). For our system, the average diameters of the peptide's ends estimated with the Swiss-PdbViewer were ∼13.2 Å (E12) and ∼18 Å (R12); knowing that the diameter of the α-HL's β-barrel is ∼20 Å, it is conceivable that the peptide's ends will still experience electrostatic interactions with the inner surface of the β-barrel, in agreement with previous findings on different systems [36,59].…”
Section: The Case Of Peptide Association To the Nanoporesupporting
confidence: 91%
“…Later, a systematic study was undertaken by Clark and co-workers to obtain more in-depth information about the translocation dynamics of unfolded protein molecules. 145 They found that the translocation of unfolded protein molecules is mainly an enthalpically driven process due to the electrostatic interaction between the protein molecules and the pore, with a minor entropy component from the confinement of the proteins within the pore.…”
Section: Biological Nanoporesmentioning
confidence: 99%
“…[18] In 2006, Aerolysin was firstly applied to analyze the structure of α-helix peptides as a nanopore sensor. [19] Subsequently, it was used to detect various molecules, including oligosaccharides, [20] peptides, [21] proteins [22][23][24] and poly (ethylene glycols) (PEGs). [25] Since the diameter of aerolysin nanopore precisely allows for the passage of single-stranded DNA, aerolysin nanopore was demonstrated that could discriminate oligonucleotides of different lengths directly and real-time monitor the stepwise cleavage of Poly(dA) 5 by Exonuclease I.…”
Section: The Effects Of Tetramethylammonium Cation On Oligonucleotidementioning
confidence: 99%